Impact of poly-γ-glutamic acid addition and pH changes on the 3D-food printability of cookie dough - Jeong, Ha Eun; Lee, Chang Joo; Min, Sea C. (Food science and biotechnology, 2025)
This study aimed to investigate the effects of poly-ɤ-glutamic acid (PGA) addition and pH adjustment on the rheological properties of cookie dough for 3D printing. Adding 1-2% PGA to the dough increased the storage modulus (G'), loss modulus (G''), shear modulus, tan δ, yield stress (τ ), phase angle, apparent viscosity, and hardness. Similarly, increasing the dough's pH from 6.0 to 8.5 enhanced G', G'', shear modulus, τ , and hardness. The addition of Alcalase to dough with high hardness modified the rheological parameters, making them to meet the required material criteria. The pH adjustment made the Alcalase treatment effective in modifying the parameters. The addition of 1% PGA or pH adjustment enabled successful 3D printing of the dough by improving fidelity, shape retention, and extrudability. Therefore, PGA addition and pH adjustment are effective methods for tailoring the physical properties of cookie dough for 3D printing applications.